Population pharmacokinetics of 17α‐hydroxyprogesterone caproate in singleton gestation. (13th July 2016) - Sharma, Shringi; Caritis, Steve; Hankins, Gary; Miodovnik, Menachem; Hebert, Mary F.; Mattison, Don; Venkataramanan, Raman
Summary: Aims: 17α‐hydroxyprogesterone caproate (17‐OHPC) reduces the rate of preterm birth in women with a prior preterm birth. Limited data exist on the pharmacokinetics (PK) of 17‐OHPC or the plasma concentrations achieved during therapy. In this study, we evaluated the population PK of 17‐OHPC in pregnant subjects with singleton gestation and also evaluated intrinsic and extrinsic factors that may potentially affect 17‐OHPC PK in this patient population. Methods: Sixty‐one women with singleton pregnancies participated in this trial. Subjects received weekly intramuscular injections of 250 mg 17‐OHPC in 1 ml castor oil from the time of enrolment (16 0/7 weeks – 20 6/7 weeks) up to 35 weeks gestation or until delivery. Blood samples were obtained between 24 and 28 weeks, between 32 and 35 weeks and over a 28‐day period beyond the last injection. Maternal and/or cord blood were obtained at delivery. Data analysis was performed by nonlinear mixed effects modelling (NONMEM ® ). Results: The 17‐OHPC PK were best described by a model with one maternal compartment and one fetal compartment, with first‐order absorption and elimination from the maternal compartment. Maternal body weight was a significant covariate for both clearance ( CL / F ) and volume of distribution ( V maternal / F ). The final population mean estimates were: CL / F 1797 l/d, V maternal / F 32 610 l and mother to cord rate constant 0.005 day −1 . This report describes for the first time the population PK of 17‐OHPC in singleton pregnancy. Conclusions: The population PK study reported here represents the initial steps in understanding and optimizing 17‐OHPC therapy for preventing preterm birth.